2023
DOI: 10.14814/phy2.15690
|View full text |Cite
|
Sign up to set email alerts
|

The effect of isometric exercise training on arterial stiffness: A randomized crossover controlled study

Abstract: Isometric exercise training (IET) is an effective intervention for the management of resting blood pressure (BP). However, the effects of IET on arterial stiffness remain largely unknown. Eighteen unmedicated physically inactive participants were recruited. Participants were randomly allocated in a cross‐over design to 4 weeks of home‐based wall squat IET and control period, separated by a 3‐week washout period. Continuous beat‐to‐beat hemodynamics, including early and late systolic (sBP 1 and sBP 2, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
(61 reference statements)
0
0
0
Order By: Relevance
“…Several studies have investigated the effects of IET on arterial stiffness, with mixed results. Okamoto et al [78] included a cohort of unmedicated physically inactive participants and reported improvements in augmentation index following 8 weeks of IET, a finding the authors have recently reproduced [196]. Differently, in a group of medicated hypertensives, Farah et al [54] found no significant pulse wave velocity or augmentation index changes after 12 weeks of IET.…”
Section: Vascular Adaptations: Structural Vascular Remodellingmentioning
confidence: 99%
“…Several studies have investigated the effects of IET on arterial stiffness, with mixed results. Okamoto et al [78] included a cohort of unmedicated physically inactive participants and reported improvements in augmentation index following 8 weeks of IET, a finding the authors have recently reproduced [196]. Differently, in a group of medicated hypertensives, Farah et al [54] found no significant pulse wave velocity or augmentation index changes after 12 weeks of IET.…”
Section: Vascular Adaptations: Structural Vascular Remodellingmentioning
confidence: 99%
“…Isometric exercise training has also been suggested as an effective intervention for inducing favorable vascular adaptations. In detail, a recent cross-over study showed that 4 weeks of isometric training (wall squats) reduced arterial stiffness (as suggested by a reduction in the augmentation index, derived from pulse-wave reflection) and total peripheral resistance [90]. In contrast, another study [91] found an improvement of microvascular function (as assessed by peak blood flow during reactive hyperemia) with dynamic resistance training (eight exercises, 50% of maximal repetition, three sets until moderate fatigue, for 10 weeks, three times/week) and not isometric handgrip training (at 30% of maximum voluntary contraction, four sets of 2 min).…”
Section: F-i-t-t Principle: T(ype)mentioning
confidence: 99%